2020
DOI: 10.5114/hpc.2020.98470
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Joint Disorder in Patients With Parkinson’s Disease – A Pilot Study

Abstract: Authors' contributionWkład autorów: A. Study design/planning zaplanowanie badań B. Data collection/entry zebranie danych C. Data analysis/statistics dane -analiza i statystyki D. Data interpretation interpretacja danych E. Preparation of manuscript przygotowanie artykułu F. Literature analysis/search wyszukiwanie i analiza literatury G. Funds collection zebranie funduszy SummaryBackground. The number of patients with temporomandibular joint disorders (TMD) is increasing in clinical dental practice. Our study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was revealed that the prevalence of TMDs was found to be 35%, exhibiting a higher occurrence among males (58%) and elderly individuals (53%) [24]. Higher occurrence of TMDs among patients diagnosed with PD was also presented in another previous crosssectional study [23]. In a previous cohort study, it was reported that a 2.11-fold increase in TMD risk exists for individuals with PD compared to healthy people [25].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It was revealed that the prevalence of TMDs was found to be 35%, exhibiting a higher occurrence among males (58%) and elderly individuals (53%) [24]. Higher occurrence of TMDs among patients diagnosed with PD was also presented in another previous crosssectional study [23]. In a previous cohort study, it was reported that a 2.11-fold increase in TMD risk exists for individuals with PD compared to healthy people [25].…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have focused on the relationship between TMJ and PD [22][23][24][25][26]. However, considering the important anatomical connections of TMJ, more studies that investigate the relationship between TMJ and PD on a morphological basis are needed for better understanding.…”
Section: Introductionmentioning
confidence: 99%
“…In total, nine studies examined unspecified TMD (viz., no clear distinction was made between TMD pain or dysfunction) in patients with PD (Table 3 ; Bakke et al, 2011 ; Baram et al, 2020 ; Baram et al, 2021 ; Baumann et al, 2020 ; Choi et al, 2021 ; Da Costa Silva et al, 2015 ; Massimo et al, 2020 ; Silva et al, 2016 ; Tavares et al, 2021 ). The within‐group results showed prevalences that varied between 1.1 and 61.7%.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, patients with PD have more difficulties with chewing than controls. Baram et al, 2020;Baram et al, 2021;Baumann et al, 2020;Choi et al, 2021;Da Costa Silva et al, 2015;Massimo et al, 2020;Silva et al, 2016;Tavares et al, 2021). The within-group results showed prevalences that varied between 1.1 and 61.7%.…”
Section: Chewing Difficultiesmentioning
confidence: 94%